Investigating the toxicity of Zataria multiflora essential oil on different stages of barnacle larvae of Amphibalanus amphitrite species - mahdie amiri nezhad; morteza yousefzadi; mitra arman; mahsa rahimzadeh (بوم‌شناسی آبزیان)
The life cycle of barnacles usually consists of two stages: the free-swimming larval stage and the stationary stage. Their larval stage has 6 stages. Considering that plant essential oils showed anti-algae properties in previous studies, in this study, the toxicity of this essential oil was investigated on different stages of barnacle larvae of A. amphitrite species. Because they should not have a negative effect on the food chain. Also, in order to evaluate the toxicity effects of Z. multiflora essential oil on barnacle larvae as a study model. This test was performed based on the determination of LC50 in a 24-hour period on different stages of barnacle larvae, in such a way that in 24-well plates of each stock, 6 concentrations of 50, 25, 12.5, 6.25, 3.125, 1.5 µg/ml was prepared, then 1 ml of sea water and 10 barnacle larvae were added to each well and the number of dead and alive was checked by loupe. The obtained results showed that the LC50-14.198 µg/ml in the (VI ( stage of and the LC50-36.91 µg/ml in the) II( stage have a significant difference. Also, this plant essential oil showed a toxic effect on barnacle larvae at concentrations higher than 20 g/ml. But in general, the use of this herbal essential oil has significant biological activity due to having carvacrol as the main component of the essential oil. Also, by having different compounds such as phenolic, terpenoids and alkaloids, it can be a pioneer in the development of practical and bio-compatible with eco-management goals in low concentrations.